Short Communication: Biocontrol activity of Phyllosphere fungi on mungbean leaves against Cercospora canescens - SUMARTINI SUMARTINI (Biodiversitas Journal of Biological Diversity, 2017)
Sumartini. 2017. Short Communication: Biocontrol activity of Phyllosphere fungi on mungbean leaves against Cercospora canescens. Biodiversitas 18: 720-726. Examination of biocontrol activity of phyllosphere fungi on mungbean leaves against Cercospora canescens, a causal agent of mungbean leaf spot disease, was conducted during February-July 2016. Samples of symptomatic mungbean leaves were collected from several production areas in East and Central Java. Symptomatic leaves with leaf spot were collected randomly by detaching the symptomatic leaves and kept in a plastic bag for laboratory studies. Fungi associated with leaf spot were isolated using surface sterilized technique on PDA medium. In vitro and in vivo antagonism assay was carried out in the laboratory and greenhouse, respectively. Fungi associated with leaf spot on mungbeans such as Fusarium spp., Curvularia spp., Aspergillus flavus, and Nigrospora sp. were tested against C. canescens in the antagonism assay. Highest inhibition activity against C. canescens was found on Fusarium sp. 2 (KH-KJP-1B) (in vitro = 61%, in vivo = 19.63%) and Curvularia sp.1 (KH-JBG-B) (in vitro = 66%, in vivo = 16.46%).